Institutions and individual values motivating corporate social responsibility activities in large farms and agroholdings - Anna Hajdu; Marcos F. Daziano; Oane Visser (International Food and Agribusiness Management Review, 2021)
Corporate social responsibility (CSR) activities have been shown to derive from external and internal motivations of a company. Little attention has been given to motivations of managers in large farms and agroholdings to undertake CSR activities thanks to individual values and pressure from institutions. We therefore investigate the types of CSR activities conducted by 18 managers in large farms and agroholdings in Argentina. We underline their perception of social issues and their motivations to do CSR activities. The framework developed in this paper shows that given the lack of pressure from national-level formal and other informal institutions, individual values (informal institutions) and international institutions (certification schemes-formal institutions) carry more weight in managers' decision to do CSR activities. While some of these motivations have an instrumental background, they overlap with normative motivations that underlie the business activity.
Keywords: M140; Q190; 650; Argentina; large-scale farms; social issues; grounded theory; large-scale land acquisitions